Collective Art Activist Practice: A Pedagogy of Hope - Desai, Dipti (Radical Teacher, 2025)
In its intent and structure collective art activist practice as a form of cultural production is pedagogical because it combines the creative power of the arts to move us emotionally with the strategic planning of activism necessary to bring about social change. Given that the goal of art activism involves some form of social action, working collectively becomes an important part of the educational process. Drawing from personal experience teaching an art activist classes as a collective in a corporate university the essay explores two questions: What does collaboration mean in artistic activism, and what can we learn about collective pedagogy for our increasingly diverse classrooms where critical DEI practices of teaching and learning in higher education should be enacted? The essay discusses the possibilities of collective pedagogy as a pedagogy of hope in the Freirian sense as well as some of the tensions and contradictions of this practice. It advocates for collective pedagogy as a prefigurative practice as it provides a space for participatory democracy as a way of living and being to be enacted in classrooms that are diverse.